Current status of African pediatric oncology education efforts aligned with the Global Initiative for Childhood Cancer. (3rd April 2023) - van Heerden, Jaques; Lisa Christine, Irumba; Downing, Julia; Davidson, Alan; Hessissen, Laila; Schoeman, Judy; Ladas, Elena J; Abdelhafeez, Hafeez; Georgia Odongo Arao, Shauna; Fentie, Atalay Mulu; Kamal, Sherif; Parkes, Jeannette; et al.
Abstract: Education of the pediatric oncology workforce is an important pillar of the World Health Organization CureAll technical package. This is not only limited to healthcare workers, but all stakeholders in the childhood cancer management process. It includes governmental structures, academic institutions, parents and communities. This review evaluated the current educational and advocacy training resources available to the childhood cancer community, the contribution of SIOP Africa in the continental educational needs and evaluated future needs to improve the management of pediatric malignancies in reaching the Global Initiative for Childhood Cancer goals. Childhood cancer, unlike adult cancers, has not been prioritized in African cancer control plans nor the teaching and advocacy surrounding pediatric oncology. The availability of formal training programs for pediatric oncologists, pediatric surgeons and radiotherapy specialists are limited to particular countries. In pharmacy and nutritional services, the exposure to pediatric oncology is limited while training in advocacy doesn't exist. Many nonacademic stakeholders are creating the opportunities in Africa to gain experience and train in these various fields, but formal training programs should still be advocated for. LEARNING POINTS: The African continent has various resources to increase the capacity of childhood cancer care stakeholders to increase their knowledge. African pediatric oncology teams rely on a multitude of international sources for training while developing their own. There is a greater need for formal, standardized cancer training especially for pediatric surgeons, radio-oncologists and nurses. Greater inclusion of pathologists, pediatric oncology pharmacists and dieticians into multidisciplinary care and childhood cancer training should be facilitated and resourced. Successful advocacy programs and tool kits exist in parts of Africa, but the training in advocacy is still underdeveloped.